Education, engagement, and youth crime: case studies in the lived experience of education and recidivism - Thoars, Cassandra (Education in the Asia-Pacific region, 2024)
This book presents insights into how affective educational experiences may be associated with youth criminal behaviour and the pathway to recidivism. It explores the perspectives and lived school experiences of five young adult male prison inmates, including while they were incarcerated as youths. Through these case studies, the book explores the relationship between affective engagement in education and recidivism. This book shows that participants were affectively disengaged from education prior to their initial incarceration in a youth detention facility, and that their disaffection before, during, and after youth incarceration both generated and impacted on their cognitive and behavioural disengagement from education. Moreover, a range of additional factors not directly causally related to their schooling were shown to have had a significant effect on their engagement in education. The book considers a number of key findings. First, the foundational role that a sense of belonging plays in how young people experience education and its relation to crime. Second, the importance of individualized transition plans for youth at risk, and youth offenders before, during, and after incarceration. Third, the extent to which successful transition from youth offending and recidivism hinges on interagency collaboration. This book will be beneficial to teacher educators, education researchers, criminologists and sociologists.